Evolution of diet patterns over time in Europe from 1963 to 2013: an exploratory analysis using PCA for compositional data vectors - Pinto, Mariana (2022)
In this study, this statistical procedure is explored to reduce the dimensionality of the evolution of diet patterns of ten countries in Europe during five decades. The main focus is on a temporal composition of the consumption in the diet of the four macronutrients.